AI vs. Human-Led Da’wah: A Comparative Rhetorical Analysis of Islamic Preaching in the Digital Age - Giffari, Haekal Adha Al; Dermawan, Andy (DINIKA : Academic Journal of Islamic Studies, 2025)
The growing use of Artificial Intelligence (AI) in religious communication has introduced new dynamics in Islamic preaching (Da’wah) as it raises questions about its linguistic, persuasive, and theological qualities compared to traditional human-led discourse. This study investigates the rhetorical characteristics of AI-generated Islamic messages by comparing them with sermons delivered by recognized Muslim scholars. The aim is to understand how AI influences the structure, authority, and effectiveness of religious messaging in the digital era. Employing a comparative rhetorical analysis, this study examines a purposive sample of AI-generated Da’wah texts and human-delivered sermons addressing similar religious themes. The analysis is grounded in Arabic rhetorical theory, Aristotelian persuasion (ethos, pathos, logos), and digital media theory to assess differences in content delivery and audience engagement. Findings show that while both forms draw on Qur’anic verses and Hadith, human preachers establish authority through years of study and community trust, whereas AI relies solely on textual citation, often defaulting to dominant interpretations. Human-led Da’wah features storytelling, emotional appeal, and context-specific reasoning, fostering deeper audience connection. In contrast, AI discourse is more neutral, informational, and lacks adaptive nuance. This study concludes that although AI can support the spread of Islamic knowledge, it falls short in replicating the rhetorical richness and relational depth of human Da’wah. These findings offer practical insights for scholars, developers, and policymakers navigating the intersection of religion and technology.